The story of a giant story. The winding way of Og king of Bashan in the Jewish haggadic tradition - Ḳosman, Admiʾel (Hebrew Union College annual / Jewish Institute of Religion, 2002)
Og, the king of Bashan, is depicted in the Bible, the midrash in the Tannaitic period and by Josephus as a giant of realistic dimensions. In the Amoraic exegeses he became a figure of monstrous proportions, possibly under the influence of views that appear in the Apocrypha. One "expansion" of his image was already delivered in the name of palestinian Amoraim, but it is linked to the dimension of time. This "stretching" could also have sparked the fertile midrashic imagination for the physical stretching of his body. In a later addition, Og became Eliezer, Abraham's servant. In the Middle Ages Og "returns" to his human dimensions, and the commentators, both the rationalists and those who engaged in esoteric interpretations, struggled to explain these exaggerated expositions as allegory. The exegesis in the Zohar and in the commentary by Rashba continue to expand the interpretive direction that presents Og as possessing spiritual merits. In the hands of the aggadic commentators in recent centuries, this direction split into two interpretive options, that share their portrayal of Og and Moses as occupying two sharply opposing poles: some refused to accept that this "wicked one" had any spiritual merits. Others sought to relate the story of Og and the story of his war with Moses as a battle between two completely righteous individuals, with the sole decisive advantage held by Moses in this struggle as being from Israel, the people that had been chosen by God.